Analysis Paralysis: Ketika Overthingking Melumpuhkan Kemandirian Akademik Mahasiswa Gen Z - Balighotul Mahbubah; Ellen Ellen (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The phenomenon of analysis paralysis can be considered one of the psychological challenges increasingly faced by Generation Z students today amidst the flood of information and academic pressure. Its signs include overthinking various options and decision-making that inhibits necessary action. This article aims to investigate the influence of analysis paralysis on the academic autonomy of Generation Z students. The research method used here is literature review. This involves analyzing relevant scientific literature regarding analysis paralysis, the characteristics of Generation Z students, and the concept of academic autonomy. The research findings indicate that overthinking can negatively impact decision-making, time management, academic task completion, and the development of students' self-confidence. As a result, academic procrastination, dependence on others, and lack of academic productivity are often experienced by students. However, improving self-regulation skills, digital literacy, time management strategies, and a positive environment in educational institutions can be beneficial in overcoming these challenges. Thus, collaborative efforts from students, lecturers, and educational institutions are needed to develop academic autonomy.